Pemikiran Tafsir Tuan Guru Haji Ismail Bin Umar dalam Kitab Mawaqif Al-marjan - Abdulloh Salaeh; Syed Najihuddin Syed Hassan; Zamrie Ibrahim @ Musa; Ahmad Kamel Mohamed; Idi Bin Hamdi (Academic Inspired Network, 2024)
Indexed by MyCite